CINNAMON, CASSIA AND ANCIENT TRADE - Stephen George Haw (Journal of Ancient History and Archaeology)
Abstract: There is a widespread assumption that ancient “cinnamon” and “cassia” were the same as the spices now known by those names; that is, products obtained from trees of the genus Cinnamomum. This article argues that this is not the case, but that the “cinnamon” and “cassia” of ancient writers very probably came from plants native to northeast Africa, as several early writers actually state. Possible African sources of ancient “cinnamon” and “cassia” are suggested. The most probable principal source is identified as Cassia abbreviata. It is also argued that alleged identifications of cinnamon or cassia at archaeological sites in the Mediterranean region are questionable. It is shown that cinnamon and cassia did not figure in Southeast Asian and Chinese trade at an early period, and that Austronesian settlement of Madagascar occurred after the Classical period, probably during the second half of the first millennium CE, too late for Southeast Asians to have played any major role in trade with the Roman Empire. There is no good reason to believe that true cinnamon and cassia were traded to the western Indian Ocean and the Mediterranean region at any very early date.   This article truly takes an interdisciplinary approach to its subject: the author is a botanist as well as a historian, and is able to use original Chinese sources. The question of whether ancient “cinnamon” and “cassia” were the same as modern cinnamon and cassia (products of trees of the genus Cinnamomum) is a thorny one, which has been repeatedly debated in the past, usually with no very conclusive result. The most recent thorough discussion of the issue, by Lionel Casson, concluded that the ancient and modern products were the same. This article refutes that view: it is clear that Casson lacked the botanical knowledge necessary to reach a sound conclusion. The article deals with its subject thoroughly, examining archaeological as well as textual evidence, and using a wide range of sources.